2002
DOI: 10.1002/aqc.476
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in diet composition and productivity of gentoo, magellanic and rockhopper penguins in the Falkland Islands

Abstract: ABSTRACT1. Over the past 14 years, data on diet composition and productivity of gentoo penguins (Pygoscelis papua), magellanic penguins (Spheniscus magellanicus) and rockhopper penguins (Eudyptes c.chrysocome) breeding in the Falkland Islands have been compiled as part of the Falkland Island Seabird Monitoring Programme. This paper comprises a summary of the data obtained so far, in particular concentrating on inter-annual and interspecific variation in productivity and general diet composition.2. Productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 14 publications
1
35
1
Order By: Relevance
“…For the last two decades, population, diet, foraging range and colony breeding success have been investigated at a number of sites across the Falkland Islands (e.g. Strange 1982;Lamey 1993;Pütz et al 2001Pütz et al , 2002Pütz et al , 2003bPütz et al , 2006Clausen and Pütz 2002;Boersma et al 2002;Huin 2005). However, its general breeding biology in the Falkland Islands has not been studied in any detail and/or over multiple years and yet it is critical to have a comprehensive understanding of the biology of the species in order to develop appropriate conservation measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the last two decades, population, diet, foraging range and colony breeding success have been investigated at a number of sites across the Falkland Islands (e.g. Strange 1982;Lamey 1993;Pütz et al 2001Pütz et al , 2002Pütz et al , 2003bPütz et al , 2006Clausen and Pütz 2002;Boersma et al 2002;Huin 2005). However, its general breeding biology in the Falkland Islands has not been studied in any detail and/or over multiple years and yet it is critical to have a comprehensive understanding of the biology of the species in order to develop appropriate conservation measures.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst southern rockhopper penguins breeding in the Indian Ocean and PaciWc Ocean almost never rear two chicks (Warham 1975;Williams 1980aWilliams , 1995Marchant and Higgins 1990;Hull et al 2004), there is evidence that suggests that it is not unusual for southern rockhopper penguin pairs in the Falkland Islands to raise two chicks (Strange 1982;Pütz et al 2001;Clausen and Pütz 2002). Strange (1982) Wrst described the general breeding biology of this species at New Island, in the western part of the Falklands Islands and both he and subsequently Lamey (1993) in the same breeding site found that more than 80% of all pairs retained both eggs until at least one hatched successfully but that most of the A-eggs or just hatched A-chicks were lost during the hatching period.…”
Section: Introductionmentioning
confidence: 99%
“…Gentoo Penguins were significantly more abundant during the nonbreeding period when open water or pack ice was present and significantly less abundant when compact ice appeared directly offshore. Past studies have indicated that Gentoo Penguins are restricted to inshore foraging during the winter months to the same extent that they are during the breeding season (Williams et al 1992, Tanton et al 2004) and have similar prey compositions during these periods (Williams 1991, Clausen andPütz 2002). We provide evidence that Gentoo Penguins on the WAP overwinter at breeding sites during periods when sea ice conditions are optimal for foraging directly inshore, using the breeding site as a resting area between foraging periods.…”
Section: Discussionmentioning
confidence: 60%
“…Gentoo Penguins are currently of interest in studies observing environmental change, as their populations are increasing at their southern limit along the Western Antarctic Peninsula (WAP), while competitor populations (Adélie and Chinstrap penguins) are declining (Lynch et al 2012). Few studies have been conducted of nonbreeding behavior, examining either winter diet (LaCock et al 1984, Williams 1991, Clausen and Pütz 2002 or winter locations using GPS or temperature loggers (Hindell 1989, Williams et al 1992, Wilson et al 1998, Tanton et al 2004, Hinke and Trivelpiece 2011. Gentoo Penguins are known to remain present at breeding sites over winter in the sub-Antarctic islands of South Georgia (Williams et al 1992), the South Shetlands (Wilson et al 1998, Hinke andTrivelpiece 2011), and Crozet Islands (see Bost and Jouventin 1990 and references therein), but there are large spatial gaps in our knowledge of their winter behavior beyond these locations, particularly comparisons between behavior at sub-Antarctic islands and the southern edge of their range on the WAP.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the Falkland Islands (52°00ЈS, 59°30ЈW) it is not unusual for E. chrysocome to raise two chicks (Strange 1982;Pütz et al 2001;Clausen and Pütz 2002). In 2006-2007, for example, three of 114 nests (2.6%) raised two chicks until Xedging (Poisbleau et al 2008).…”
Section: Introductionmentioning
confidence: 99%